The Effect of Glucose or Fructose Added to a Semi-solid Meal on Gastric Emptying Rate, Appetite, and Blood Biochemistry - Evans, Gethin H.; McLaughlin, John; Yau, Adora M. W. (Frontiers in Nutrition, 2018)
The ingestion of fructose is of interest due to previously reported differences in gastrointestinal, appetite and metabolic effects when compared to glucose ingestion when ingested in liquid solution. The aim of this study was to examine these variables when fructose and glucose are added to a semi-solid meal. Seven healthy male participants completed three experimental trials involving the ingestion of 300 mL of semi-skimmed milk mixed with 40 g of instant porridge mix (CON) and with the addition of either 40 g of glucose (GLU) or fructose (FRU). Subjective feelings of appetite were assessed for two hours after ingestion with blood samples collected at regular intervals. Gastric emptying rate was assessed using the 13C breath test method. Half emptying time was not different between trials (CON = 159 ± 51 min; GLU = 197 ± 46 min; FRU = 198 ± 67 min: P = 0.117). No differences were observed for any subjective measurements of appetite (P > 0.05) while blood glucose was elevated (P < 0.05) 20 minutes after ingestion on both GLU and FRU with this tending to be higher on GLU than FRU. FRU resulted in greater (P < 0.05) blood lactate concentrations than on the other trials. The results of this study demonstrate that gastric emptying rate of glucose and fructose is similar when ingested in a semi-solid meal. In addition, there is little difference in appetite response between these sugars, however, there are some differences in metabolic response which deserve further study.